2016
DOI: 10.3928/01913913-20160818-01
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pediatric Aphakic Glaucoma With Vitrectomy and Tube Shunts

Abstract: Combined vitrectomy and placement of a glaucoma tube shunt can be safe and effective in lowering IOP based on mean IOP values and number of glaucoma medications at 1 year. [J Pediatr Ophthalmol Strabismus. 2016;53(6):339-343.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We did not routinely encounter vitreous in the anterior chamber because all cataract surgeries were performed with vitrectomy with the removal of a posterior vitreous border membrane. However, over time, the posterior vitreous may become loose and may incarcerate the tube in aphakic eyes where there was aphakic without vitrectomy at the time of the GDD implantation [21][22][23][24]. Vigilant observation for incarceration is required over the patient's lifetime, along with appropriate treatment [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not routinely encounter vitreous in the anterior chamber because all cataract surgeries were performed with vitrectomy with the removal of a posterior vitreous border membrane. However, over time, the posterior vitreous may become loose and may incarcerate the tube in aphakic eyes where there was aphakic without vitrectomy at the time of the GDD implantation [21][22][23][24]. Vigilant observation for incarceration is required over the patient's lifetime, along with appropriate treatment [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…However, over time, the posterior vitreous may become loose and may incarcerate the tube in aphakic eyes where there was aphakic without vitrectomy at the time of the GDD implantation [21][22][23][24]. Vigilant observation for incarceration is required over the patient's lifetime, along with appropriate treatment [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…GDD is applied in the anterior chamber as a shunter to draw the aqueous humor through a tube to a subconjunctival end-plate, including valved (Ahmed glaucoma valve) and nonvalved (Molteno and Baerveldt implants) designs. GDD implantation is currently among the most widely used treatments for GFCS 23,81,85,89–100…”
Section: Treatmentmentioning
confidence: 99%
“…GDD implantation is currently among the most widely used treatments for GFCS. 23,81,85,[89][90][91][92][93][94][95][96][97][98][99][100] A success rate of up to 95% has been achieved; however, there is no consensus on the diagnostic criteria of success. Several studies have demonstrated that success rate decreases with time.…”
Section: Gdd Implantationmentioning
confidence: 99%
“…Some recent studies tend to choose glaucoma drainage devices (GDD), such as Ahmed glaucoma valve (AGV), as first-line procedure because of their favourable risk profile and long-term success. 1417…”
Section: Introductionmentioning
confidence: 99%